(untitled) (Tempo e Argumento, 2021)
The interest in historicizing the present time in Mexico has been increasing in recent years. This means that History of the Present Time has become a subdiscipline in the consolidation that undergoes a process of definition and outline of its own. This article aims to discuss and analyze the building and the state-of-the-art of this subdiscipline in the country: to characterize the literature and take a quick stock of its areas of interest, challenges, and possible research agendas. To do this, in addition to defining what we understand as History of the Present and addressing the emergency conditions in Mexico, we share a qualitative research work on the literature review of Mexican indexes of specialized Social Science journals. Thanks to this work, we outline characteristics of the historical present as a field in the country, noticing the gradual consolidation and institutionalization of this subdiscipline and pointing out similarities and differences in relation to the field in Latin America. Keywords: history of the present time; Mexico; historiography; interdiscipline; institutionalization.